EFIKASI KONSENTRASI INSEKTISIDA BERBAHAN AKTIF Bacillus thuringiensis DAN Emamektin Benzoat TERHADAP ULAT BAWANG (Spodoptera exigua) PADA TANAMAN BAWANG DAUN (Allium fistulosum L.) - Karya; Wisnu Ginanjar Supriyadi (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2021)
This aims of this research to see the efficacy of several concentrations of pesticides with active ingredients Bacillus thuringinensis and Emamectin Benzoate which can provide the best effect on the control of Spodoptera exigua pest attack on onion plants (Allium fistulosum L.). The experiment was carried out in the Pangalengan District, Bandung Regency. Located at an altitude of 1100 meters above sea level (msl), the texture of the clay is dusty with a pH of 5.44 and a rainfall of 2904.7 mm / year, including type C2 based on Oldeman's 1975 classification. The trial period is from April to July. 2018. The research method used an experimental method with a randomized block design (RBD) consisting of A (Control. 0.00 ml / liter of water or without insecticide), B (Florbac FC 0.25 ml / liter of water for the active ingredient Bacillus thuringiensis), C (Florbac FC 0 , 75 ml / liter of water for the active ingredient Bacillus thuringiensis), D (Florbac FC 1.25 ml / liter of water for the active ingredient Bacillus thuringiensis), E (Prothol 10 EC 0.25 ml / liter of water for the active ingredient Emamectin benzoate), F (Prothol 10 EC 0 , 75ml / liter of water for the active ingredient Emamectin benzoate) and G (Prothol 10 EC 1.25 ml / liter of water for the active ingredient Emamectin benzoate). The results showed that giving a concentration of Prothol 10 EC 1.25 ml / liter of water the active ingredient Emamectin benzoate gave a better effectiveness value in controlling the Spodoptera exigua pest with an effectiveness value of 44.50% and treatment of the concentration of Florbac FC 1.25 ml / liter of water as the active ingredient Bacillus thuringiensis with an effectiveness value of 37.78%.